Repercussões da lei do feminicídio sobre a mortalidade de mulheres por violência no Brasil - Machado, Jorge Luis Ribeiro (2024)
This dissertation aims to analyze the possible repercussions of Law no. 13,104/2015 (Feminicide Law) on the mortality of women due to violence in Brazil from 1989 to 2021 with a view to identifying whether there has been a reduction in the number of homicides committed against women. To this end, it addressed topics such as genderbased violence in Brazil, with an emphasis on the types and cycle of violence against women; and feminicide as the last stage of Domestic and Family Violence Against Women (VDFCM), addressing coping networks and the importance of Emergency Protective Measures (MPU). Regarding the methodology, bibliographic and documentary research was used. The data was extracted from the website of the Institute for Applied Economic Research (IPEA), which provides information on homicides by gender in all federative units in Brazil. The period defined for the research was from the year 1989 to the year 2021. Considering that the objective of the work will be to identify whether after the Feminicide Law and the increase in the penalty for the aggressor were relevant to contain the number of homicides committed against women, Initially, the average number of homicides of women committed from 1989 to 2014 was analyzed, comparing, secondly, with the average number of homicides of women that occurred between 2015 and 2021. It was found that after the Law in 13,104/2015, the average number of homicides of women occurring per year increased after the Feminicide Law, which demonstrates that after the enactment of the Law there was no reduction in the rates of homicides committed against women. It was concluded that to prevent feminicide, it is crucial to address domestic violence at its roots, implementing far beyond laws, but also effective public policies, providing adequate support to victims, making MPU effective and promoting a culture of gender equality and respect for women's rights. Education and awareness are also essential to challenging and changing attitudes and beliefs that perpetuate violence against women.